2009
DOI: 10.1590/s0073-47212009000400007
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura populacional de Uca maracoani (Decapoda, Brachyura, Ocypodidae) no Baixio Mirim, Baía de Guaratuba, Paraná

Abstract: ABSTRACT. Population structure of Uca maracoani (Decapoda, Brachyura, Ocypodidae) from the tidal flat of Baixio Mirim, Guaratuba Bay, Parana State, Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
(32 reference statements)
0
6
0
4
Order By: Relevance
“…Hirose and Negreiros-Fransozo (2008) reported low reproduction rates during the summer and suggested that high temperatures and low salinities prevent individuals from exiting their burrows and copulating, thus regulating their reproductive behavior. U. maracoani reproduces throughout the year, as shown by the presence of females with eggs along the whole year with two intense reproductive peaks in April (autumn) and November (spring) (Di Benedetto et al 2009). This result suggests that observed seasonal differences in the antioxidant capacity of U.…”
Section: )mentioning
confidence: 99%
“…Hirose and Negreiros-Fransozo (2008) reported low reproduction rates during the summer and suggested that high temperatures and low salinities prevent individuals from exiting their burrows and copulating, thus regulating their reproductive behavior. U. maracoani reproduces throughout the year, as shown by the presence of females with eggs along the whole year with two intense reproductive peaks in April (autumn) and November (spring) (Di Benedetto et al 2009). This result suggests that observed seasonal differences in the antioxidant capacity of U.…”
Section: )mentioning
confidence: 99%
“…However, ovigerous females and juveniles were found all year round, with higher frequencies in autumn, winter and spring, revealing a continuous reproduction period. The sub-tropical population analyzed by Benedetto & Masunari (2009) also shifted between unimodal in autumn, spring and winter and bimodal in summer. Ovigerous females were found throughout the year and the juvenile recruitment was also continuous, with two periods of intensity.…”
Section: Discussionmentioning
confidence: 89%
“…maracoani are known to date (Crane, 1958(Crane, , 1975Rosenberg, 2001;Masunari et al, 2005;Hirose & Negreiros-Fransozo, 2007;Thurman et al, 2013). However, although it is a large and common species, there are only three known studies on its population and reproductive aspects, one in the Amazon region (Koch et al, 2005) and two of which were conducted in the subtropical coast of southeastern Brazil by Hirose & Negreiros-Fransozo (2008) and by Benedetto & Masunari (2009).…”
Section: Introductionmentioning
confidence: 99%
“…is often different from 1:1, males being usually more abundant than females. However, there are several Brazilian populations of Uca with sex ratio of 1:1; for instance Uca (Minuca) thayeri Rathbun, 1900 and Uca (Leptuca) leptodactyla Rathbun, 1898 studied by Bezerra andMathews-Cascon (2006 and2007, respectively), Uca (Minuca) rapax Smith, 1870 by Castiglioni et al (2006), Uca (Uca) maracoani Latreille, 1802-1803 by Hirose and Negreiros-Fransozo (2008) and by Di Benedetto and Masunari (2009) and Uca (Minuca) mordax (Smith, 1870) by Fransozo et al (2009). Valiela et al (1974) and Emmerson (1994) reported that the deviation of sex ratio from 1:1 seems to be related to the reproductive system of fiddler crabs: because males spend more time on the surface defending territory and performing waving to attract females, they are more visible and therefore more susceptible to predation.…”
Section: Sex Ratiomentioning
confidence: 99%